Gambaran Penggunaan Vitamin C Sebagai Imunomodulator Pada Pasien Dewasa Dengan Covid-19: Studi Literatur - Luh Tuti Suryati; Debby Juliadi (Jurnal Farmasi & Sains Indonesia, 2021)
Corona virus or COVID 19 is a virus that causes disease in animals or humans. COVID-19 more often attacks the respiratory tract. Improving the immunity of COVID-19 patients is very much needed because the treatment for COVID-19 has not been found. Vitamin C is a vitamin that can prevent and treat respiratory infections by enhancing various immune cell functions. Vitamin C acts as a powerful antioxidant and helps replace damaged cells so it can help with COVID-19. This literature study aims to determine the use of vitamin C as an immunomodulator in adult COVID-19 patients. The data collection method was obtained by reviewing 10 journals using Google Scholar and Pubmed using English-language journals. The keywords used are vitamin C, COVID-19, treatment. The results obtained in the form of intravenous vitamin C with a dose of can improve the lives of COVID-19 patients by increasing the immunity of infected patients. This can be seen from the inhibition of the development of cytokines and an increase in lymphocytes and CD4+ T cells. In addition, it improves the patient's respiratory function with an increase in PiO2/FiO2.